Burning mouth syndrome: A review - Rajendra G Patil; Udita Singh; Ganapathi Moger; Simi Thankappan (Wolters Kluwer Medknow Publications, 2017)
Burning mouth syndrome is a condition characterized by chronic orofacial pain without any mucosal abnormalities or other organic disease. There are numerous synonyms for this ailment such as stomatodynia, stomatopyrosis, glossodynia, glossopyrosis, sore mouth, sore tongue, oral dysesthesia, and scalding mouth syndrome. Patients usually present with burning, stinging, or numbness on the tongue or other areas of oral mucosa. The complex etiology and lack of characteristic signs and symptoms makes the diagnosis difficult. As a result of which managing such patients become a herculean task. Moreover, lack of understanding of the disease leads to misdiagnosis and unnecessary referral of patients. In this article, the authors have described the etiopathogenesis, diagnostic algorithm and management of this confusing ailment.